Associations of Organizational Justice with Tinnitus and the Mediating Role of Depressive Symptoms and Burnout—Findings from a Cross-Sectional Study - Herr, Raphael M.; Loerbroks, Adrian; Bosch, Jos A.; Seegel, Max; Schneider, Michael; Schmidt, Burkhard (International Journal of Behavioral Medicine, 2016)
Background: Tinnitus refers to the perception of a sound while an external source is absent. Research has identified work-related stress and its potential mental health-related sequelaes, i.e., depression and burnout, as risk factors for tinnitus. Perceived unfairness at work (organizational injustice), which is considered a psychosocial occupational stressor, has been shown to predict depression and burnout but its potential associations with tinnitus remains unaddressed. Purpose: The aim was to determine the relationship of organizational injustice with tinnitus, and to examine depression and burnout as potential mediators. Method: Cross-sectional data from a sample of 1632 employees were used. Tinnitus was assessed by self-report (n = 207; 13.9 %). Organizational justice and its subcomponents (interactional and procedural justice), burnout, and depressive symptoms were measured by validated questionnaires. Associations were assessed by logistic regressions, and mediation was assessed by maximum likelihood logistic regression estimations. Results: Overall organizational justice, interactional and procedural justice were inversely related to tinnitus (z-score for overall justice: OR = 0.754; 95 % CI = 0.649 to 0.876). These associations were independent of demographics, socioeconomic status, job characteristics (including potential noise exposure), and health behaviors. Mediation analyses suggested a potential mediation by burnout (95 % CI indirect effect −0.188 to −0.066) and depressive symptoms (95 % CI indirect effect −0.160 to −0.043). Parallel multiple mediation analysis revealed that mediation through burnout was significantly larger than through depressive symptoms. Conclusion: Organizational justice appeared inversely related to tinnitus and this association was explained by individual differences in burnout symptoms, suggesting mediation. Longitudinal studies may further help to strengthen the evidence base for prevention of tinnitus through promotion of organizational justice and prevention of burnout.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Burnout; Depressive symptoms; Mediation; Organizational justice; Tinnitus; Work stress